2021
DOI: 10.3390/jcm10122566
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Performance between ARC-HBR Criteria and PRECISE-DAPT Score in Patients Undergoing Percutaneous Coronary Intervention

Abstract: The proper management of bleeding risk in patients undergoing percutaneous coronary intervention (PCI) is critical. Recently, the Academic Research Consortium for High Bleeding Risk (ARC-HBR) criteria have been proposed as a standardized tool for predicting bleeding risk. We sought to compare the predictive performance of ARC-HBR criteria and the PRECISE-DAPT score for bleeding in Korean patients undergoing PCI. We recruited 1418 consecutive patients undergoing PCI from January 2012 through December 2018 (Dong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 24 publications
1
6
0
3
Order By: Relevance
“…NSAIDs or steroids were moderately prevalent. Previous studies have reported similar results [ 14 , 19 , 20 , 21 , 22 , 23 , 24 ]. OAC-use and age seem to be even more prevalent in Finnish patients, but active malignancy is less frequently encountered.…”
Section: Discussionsupporting
confidence: 79%
See 4 more Smart Citations
“…NSAIDs or steroids were moderately prevalent. Previous studies have reported similar results [ 14 , 19 , 20 , 21 , 22 , 23 , 24 ]. OAC-use and age seem to be even more prevalent in Finnish patients, but active malignancy is less frequently encountered.…”
Section: Discussionsupporting
confidence: 79%
“…The prevalence of HBR according to ARC–HBR criteria in studies of European and Asian populations has ranged from 30% to 50%, and the incidence of major bleeding events in the HBR groups of these studies has consistently been ≥4% at 1 year [ 14 , 19 , 20 , 21 , 22 , 23 , 24 ]. The highest major bleeding rates were reported in Korea.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations